Reading in The Digital Era : How Parent’s Academic Background and Self-Efficacy Influence Children’s Reading Habits - Ana Ratnasari; Asep Herry Hernawan; Laksmi Dewi (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study aims to analyze the relationship between parental educational background, self-efficacy, and children's reading habits in the digital era. Using a correlational quantitative research method, the study involved 408 parents in West Jawa with children aged 4–8 years. The sampling technique used was multistage random sampling. Data were collected through an online Likert-scale questionnaire and analyzed using ordinal logistic regression. The findings indicate that parental self-efficacy significantly influences children's reading habits (B = 0.247; p < 0.001), while parental educational background does not have a direct significant effect (p > 0.05). The model's Nagelkerke R² value of 0.494 suggests that 49.4% of the variance in children's reading habits can be explained by parental self-efficacy and educational background. These results highlight the importance of parental confidence in supporting children's literacy, which can be enhanced through family literacy intervention programs. Thus, this study contributes new insights into the psychological and environmental factors affecting children's reading habits.